Origanum majorana L.: A Nutritional Supplement With Immunomodulatory Effects - Wang, Senye; Zhou, Li; Attia, Fatma Al-Zahra K. K.; Tang, Qi; Wang, Mengke; Liu, Zhenhua; Waterhouse, Geoffrey I. N.; Liu, Lijun; Kang, Wenyi (Frontiers in Nutrition, 2021)
Origanum majorana L. is an aromatic herb that has been grown in several Mediterranean countries since ancient times, but became popular during the Middle Ages as a medicinal plant and seasoning ingredient. O. majorana has many pharmacological effects, but its immunoreactive components and mechanisms are still unclear. In this study, four compounds were isolated and identified from O. majorana by a spectral analysis, including 1H and 13C-NMR. They were 1H-indole-2-carboxylic acid (1), (+)-laricresol (2), (+)-isolaricresol (3), and procumboside B (4, pB), which were isolated for the first time in O. majorana. The immunomodulatory effects of the four compounds were screened, and pB had good immunomodulatory activity on RAW 264.7 cells. The immunomodulatory mechanism of pB was proved, in which pB could increase the secretion of nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and reactive oxygen species (ROS) and simultaneously upregulate the expression of CD80 and CD86 on the cell surface. These results suggested that the mechanism of pB may be related to the activation of nuclear factor-kappaB (NF-κB) and mitogen-activated protein kinases (MAPKs)-signaling pathways. O. majorana is rich in nutrients and is commonly used in diets, so it can be used as a nutritional supplement with immunomodulatory effects.